UMPSA achieves 5-star success in MyMoheS rating - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 14 August 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recorded a proud achievement when it obtained a 5-star rating for MyMoheS, as announced during the Data Quality Meeting No. 2/2025 at Universiti Sains Malaysia (USM), Penang on 14 August 2025 recently.